Study of the Importance of Contemporary Iranian Traditional Handmade Dolls and Puppets - Azadeh Nikouei,; Mahin Sohrabi Nasirabadi, (Wacana Seni Journal of Arts Discourse, 2016)
Dolls and puppets are more than decorative objects; as part of the earliest relics, they have played many roles in society. This study deals with the functions and aesthetics of Iranian dolls and puppets in art and humanity to show their importance. In most cases today, the dolls are at risk of vanishing. Based on regional diversity, abundance and currency, five examples have been chosen for analysis. The dolls and puppets are assessed semiotically through the descriptive analytic system. The discussion also examines the process of elimination, exaggeration and stylisation, and the dolls' ability as a cognate medium for advertising other types of traditional arts. Finally, through inductive analysis, the findings suggest that dolls preserve traditions and tribal identity from homogenisation.